2011
DOI: 10.1063/1.3670361
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries and multiferroic properties of novel room-temperature magnetoelectrics: Lead iron tantalate – lead zirconate titanate (PFT/PZT)

Abstract: Mixing 60-70% lead zirconate titanate with 40-30% lead iron tantalate produces a single-phase, low-loss, room-temperature multiferroic with magnetoelectric coupling: (PbZr0.53Ti0.47O3) (1-x)- (PbFe0.5Ta0.5O3)x. The present study combines x-ray scattering, magnetic and polarization hysteresis in both phases, plus a second-order dielectric divergence (to epsilon = 6000 at 475 K for 0.4 PFT; to 4000 at 520 K for 0.3 PFT) for an unambiguous assignment as a C2v-C4v (Pmm2-P4mm) transition. The material exhibits squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 46 publications
7
90
1
Order By: Relevance
“…It has been known for several years [1][2][3][4][5][6] that the perovskite oxides PbFe 1/2 Ta 1/2 O 3 (PFT), PbFe 1/2 Nb 1/2 O 3 (PFN), and PbFe 2/3 W 1/3 O 3 (PFW) are multiferroics with long-range magnetic ordering near or above room temperature. Our earlier studies showed [7][8][9][10][11][12][13][14][15][16][17] that solid solutions of these materials with PbZr x Ti 1Àx O 3 and pure PbTiO 3 yielded single-phase ferroelectric crystals whose weak ferromagnetism persists to room temperature or above. The low electrical conductivity of these materials thus produced a good alternative to BiFeO 3 for commercial device materials with intended embodiments as multiferroic memories, 18-21 sensors, 22 or voltage-controlled magnetic tunnel junctions [23][24][25] or THz generators.…”
mentioning
confidence: 99%
“…It has been known for several years [1][2][3][4][5][6] that the perovskite oxides PbFe 1/2 Ta 1/2 O 3 (PFT), PbFe 1/2 Nb 1/2 O 3 (PFN), and PbFe 2/3 W 1/3 O 3 (PFW) are multiferroics with long-range magnetic ordering near or above room temperature. Our earlier studies showed [7][8][9][10][11][12][13][14][15][16][17] that solid solutions of these materials with PbZr x Ti 1Àx O 3 and pure PbTiO 3 yielded single-phase ferroelectric crystals whose weak ferromagnetism persists to room temperature or above. The low electrical conductivity of these materials thus produced a good alternative to BiFeO 3 for commercial device materials with intended embodiments as multiferroic memories, 18-21 sensors, 22 or voltage-controlled magnetic tunnel junctions [23][24][25] or THz generators.…”
mentioning
confidence: 99%
“…3 ('PZT') have been under study for several years in a San Juan-Cambridge-Belfast collaboration that now includes Delhi. [32][33][34][35][36][37][38][39][40] The reason is shown in the Venn diagram in Figure 4. Each of the Fe-compounds is ferromagnetic at modest temperatures and ferroelectric at low temperatures.…”
Section: Copper Oxidementioning
confidence: 99%
“…The PFW/PZT system was studied in some detail both theoretically and experimentally [31][32][33] and exhibits a polarization P(H) that is strongly dependent upon magnetic field (H), collapsing abruptly for H near 1.0 T ( Figure 5). However, the data on dielectric loss e 0 (H) ( Figure 6) show that this is because H changes the response time of the system, and hence this is a purely relaxational dynamic effect.…”
Section: Lead-iron Perovskitesmentioning
confidence: 99%
“…For x = 0.1 to 0.4 this solid solution exhibits saturated ferroelectric hysteresis loops with saturation polarization about 25 to 40 µC/cm 2 and square saturated magnetic hysteresis loops with magnetization 0.1 emu/g at 295 K (i.e. weak ferromagnetism) [7][8][9]. It means that PZT-PFT belongs to the class of materials known as multiferroics.…”
Section: Introductionmentioning
confidence: 99%
“…It means that PZT-PFT belongs to the class of materials known as multiferroics. Moreover, PZT-PFT is the lowest-loss room-temperature multiferroic known [7,9]. Such materials are very interesting for magnetoelectric devices.…”
Section: Introductionmentioning
confidence: 99%